The advent of a pan-collagenous CLOVIS POINT for pathotropic targeting and cancer gene therapy, a retrospective - Gordon, Erlinda M.; Hall, Frederick L. (Frontiers in Molecular Medicine, 2023)
The ‘Clovis Point’—an enabling prehistoric gain-of-function in stone-age tool technologies which empowered the Paleoindian-Americans to hunt, to strike-deep, and to kill designated target megafauna more efficiently—was created biochemically by molecular-genetic bio-engineering. This Biomedical “Clovis Point” was crafted by adapting a broad-spectrum Pan-Collagen Binding Domain (Pan-Coll/CBD) found within the immature pre-pro-peptide segment of Von Willebrand Factor into a constructive series of advanced medical applications. Developed experimentally, preclinically, and clinically into a cutting-edge Biotechnology Platform, the Clovis Point is suitable for 1) solid-state binding of growth factors on collagenous scaffolds for improved orthopedic wound healing, 2) promoting regeneration of injured/diseased tissues; and 3) autologous stem cell capture, expansion, and gene-based therapies. Subsequent adaptations of the high-affinity Pan-Coll/CBD (exposed-collagen-seeking/surveillance function) for intravenous administration in humans, enabled the physiological delivery, aka Pathotropic Targeting to diseased tissues via the modified envelopes of gene vectors; enabling 4) precision tumor-targeting for cancer gene therapy and 5) adoptive/localized immunotherapies, demonstrating improved long-term survival value—thus pioneering a proximal and accessible cell cycle control point for cancer management—empowering modern medical oncologists to address persistent problems of chemotherapy resistance, recurrence, and occult progression of metastatic disease. Recent engineering adaptations have advanced the clinical utility to include the targeted delivery of small molecule APIs: including taxanes, mAbs, and RNA-based therapeutics.